Electrotherapy for the treatment of brain tumours - Branter, Joshua (2020)
Introduction The scarcity of effective treatment options for high grade brain tumours has led to a wide ranging search for alternative means of therapy for these difficult to treat tumours. Electrical field therapy is one such area that has been considered. The OptuneTM system is an FDA approved novel anti-mitotic device that delivers continuous alternating electric fields to the patient for the treatment of primary and recurrent Glioblastoma multiforme (GBM) (TTFields). Alternative electric fields delivery systems are also being investigated for the treatment of various cancers. Here we present our explorative study into the feasibility of repurposing deep brain stimulating (DBS) electric fields for the treatment of brain tumours, as well as our investigations into the effects of TTFields on paediatric brain tumour cell lines.